Badanie Nośności Zbiorników Opartych na Siodłach - Kacperski, T. (Engineering Transactions, 1971)
A discussion of the results of experiments and the method of conducting them on models of horizontal, one-storied containers placed on what are called saddles. The character of the change of limiting load capacity of the containers is presented as depending on the position of the saddles on the jacket. It is shown that the force causing loss of stability in the jacket compressed by the saddles decreases very rapidly at a very small distance from the bottoms. Only after the saddles exceed a definite distance from the bottom does decrease of the values of this force begin to proceed more slowly.The results of the investigations performed enable conclusions to be drawn concerning applications of this kind of structure. As regards the widespread use of containers set up it this way the results of the tests discussed may be useful.